Vidros fosfatos com tungstênio: incorporação de cátions alcalinos e sua influência nas propriedades estruturais e condutoras - Munhoz, João Fernando Villarrubia Lopes (2018)
Many glasses have been studied as solid electrolytes in behalf of replacing commercial liquid electrolytes. However, even for the best glass compositions available in the literature, values of conductivity similar to those presented by liquids are far beyond to be achieved. This work intends to show how changes in the structure, by means of composition, can help to increase the conductivity in oxide glasses. Samples with composition x WO3 - 0.30 (NaPO3)n - (0.70-x) NaF, with 0,30 ≤ ≤ 0,60;, were produced by melting quenching methodology. Substitution of tungsten for sodium fluoride generates a linear decrease of glass transition temperature while the stability remains high enough up to = % and decreasing for higher WO3 content. Raman and 31P and 19F 1D MAS-NMR spectroscopies data shows that the less NaF leads to a depolymerization of main phosphate chains, due to formation of − − bonds. In addition, fluorine atoms prefer to bind in the − form, with low tungsten content, or in − , with high proportion All samples showed same calculated values of Ea for ionic conductivity and drop of σ0. For higher fluoride proportion, it was observed a rise in the conductivity of around one order of magnitude. However, UV-Vis absorption curves demonstrate more presence of W5+ species in samples with ≥ %. This leads to a mixed conductivity of these materials. In order to obtain maximum ionic conductivity, NaF and (NaPO3)n were replaced by Li2O and (LiPO3)n respectively. Samples with composition x WO3 – 0.40 (LiPO3)n – (0.60-x) Li2O, with 0.30 ≤ ≤ 0.50; 0.40 WO3 – y (LiPO3)n – (0.60- y) Li2O, with 0.30 ≤ ≤ 0.50 and z WO3 – (0.80-z) (LiPO3)n – 0.20 Li2O, with 0.30 ≤ ≤ 0.50; were also produced using the melting quenching methodology. The three series of samples presented linear increase of Tg with their respective substitutions, besides having good thermal stability (> 100 °). Raman and 31P 1D MAS-NMR spectroscopies data exhibited the influence of WO3 content on the depolymerization of phosphate chains, as well as the formation of WO6 unit clusters, when much tungsten is present. Although UV-Vis absorption spectra indicate mixed conductivities in some samples, calculated values of ionic conductivity show that the most conductive sample without presence of reduced species reached 6.3 10−4Ω−1−1, comparable to conductive crystalline samples.